Makna dan fungsi tuturan register dalam games online â€œmobile legendâ€ serta pengaruhnya bagi gamers - Elen Inderasari; Kalpika Cahya Buana; Riza Marâ€™atus Sholikhaha (Universitas Ahmad Dahlan, 2020)
Mobile Legend is a type of online games that uses communication between players. The purpose of this study was to determine the form, meaning and function of register speech that gamers made when playing Mobile Legend games, and to determine the positive and negative impacts for gamers. This type of research is descriptive qualitative, which describes the data obtained. This research data is the form of speech used by gamers in Mobile Legend. Data obtained from listening, taking notes, and documentation. Data analysis in this research was done by collecting data, reducing data, classifying data, presenting data, and concluding data. Based on the results obtained that there are various types of register speeches, each of which contains a special meaning that has been agreed upon and understood by both parties between Games Mobile Legend players so that communication is effective. The speech function delivered is nothing but to establish communication so that the match runs smoothly. Based on its function, it can be classified based on its speech function, which is divided into 7 categories, namely speech that serves to warn the team because it is being attacked, invite to play Mobile Legend games, order the team to attack or retreat, praise the team or other players, criticize other teams or players , declare the team's victory, and declare the team's defeat. The good and bad effects of this game on players in terms of language, action, thinking, and social to the surrounding environment.